Pengaruh Cost Leadership Dan Differentiation Strategy Terhadap Citra Produk PT. Asuransi Bumi Putra 1912 - Sabar Napitupulu (LPPM Swadaya Institute of Business and Communication, 2022)
The results of the contemporaneous test between the Cost leadership Strategy and Isolation contemporaneously on Product Image, contemporaneously0.745 therefore there's a strong positive relationship the results of the direct retrogression test Y = 7.8950.647 X10.133 X2 the test results show the pure value of the image variable of7.895 while the donation of the Cost leadership variable is0.647 and the donation of the isolation variable is0.133 therefore the donation value of Costleadership is more dominant than the isolation variable, the results of the thesis test show Fhitung29.259> Ftabel also( Ha) is accepted with ρ = 0.000< α = 0.05 so it can be concluded that Costleadership and Isolation contemporaneously